Tanggung Jawab BPN Terhadap Perbedaan Informasi Keadaan dan Rencana Penggunaan Tanah pada Sertipikat dengan Informasi Tata Ruang - Tara Diva, I Gusti Agung Bagus Yudara; Astariyani, Ni Luh Gede (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024), 2024)
The aim of this research is to understand the land registration system in Indonesia, as well as to analyze the implications of the negative publication principle for Indonesian National Land Office coverage of disputes that arise due to differences in information about the condition and land use plans on the certificate and spatial planning information. This research uses Normative legal research method with a statute approach and a conceptual approach by analyzing the negative publication system in land registration and Indonesian National Land Office responsibility for the certificates it issues if there is a difference between the data in the measurement letter and the spatial planning information. This research shows that the negative publication system adopted in land registration in Indonesia certainly means that the state does not guarantee the truth of information about the conditions and plans for land use. So Indonesian National Land Office cannot be asked to be responsible for differences in the information in the measurement letter and the spatial planning information